Organization of two invariant surface glycoproteins in the surface coat of Trypanosoma brucei. - Ziegelbauer, K (1993)
The surface coat of Trypanosoma brucei, formed by about 10(7) molecules of the membrane-form variant surface glycoprotein (mfVSG) per cell, is generally considered to constitute a barrier against the access of antibodies directed to invariant surface proteins. The recent characterization of two invariant surface glycoproteins (ISGs) with apparent molecular masses of 65 and 75 kDa (ISG65 and ISG75; 70,000 and 50,000 molecules per cell, respectively), which are both predicted to be composed of large extracellular domains, single transmembrane alpha-helices, and small intracellular domains, enabled a critical test of this hypothesis. Although ISG65 is distributed over the entire surface of the parasites, it is not accessible to antibodies or to the proteinase trypsin in live cells provided the mfVSG is also proteinase resistant. ISG75 is similarly distributed; its accessibility to antibodies depends on the expressed mfVSG, and it is sensitive to trypsin in a variant clone in which the mfVSG is proteinase resistant. Vaccination experiments using recombinant proteins to a mixture of the native ISGs were unsuccessful. ISG65 but not ISG75 elicited an antibody response in chronically infected mice. The results strengthen the view of the protective properties of the variant surface glycoprotein coat by steric hindrance and suggest that additional factors such as low abundance or low immunogenicity of invariant surface proteins may prevent a control of the disease by the humoral immune response.